Degenerative Changes in the Knee 2 Years After Anterior Cruciate Ligament Rupture and Related Risk Factors: A Prospective Observational Follow-up Study. (June 2016) - van Meer, Belle L.; Oei, Edwin H.G.; Meuffels, Duncan E.; van Arkel, Ewoud R.A.; Verhaar, Jan A.N.; Bierma-Zeinstra, Sita M.A.; Reijman, Max
Background: Anterior cruciate ligament (ACL) rupture is a well-known risk factor for development of knee osteoarthritis. Early identification of those patients at risk and early identification of the process of ACL rupture leading to osteoarthritis may aid in preventing the onset or progression of osteoarthritis. Purpose: To identify early degenerative changes as assessed on magnetic resonance imaging (MRI) after 2-year follow-up in patients with a recent ACL rupture and to evaluate which determinants are related to these changes. Study Design: Cohort study; Level of evidence, 2. Methods: Included in this study were 154 adults aged between 18 and 45 years with acute ACL rupture diagnosed by physical examination and MRI, without previous knee trauma or surgery, and without osteoarthritic changes on radiographs. A total of 143 patients completed the 2-year follow-up, and the results in this study apply to these 143 patients. All patients were treated according to the Dutch guideline on ACL injury. Of the 143 patients, 50 patients were treated nonoperatively during the 2-year follow-up period. Main outcome was early degenerative changes assessed on MRI defined as progression of cartilage defects and osteophytes in tibiofemoral and patellofemoral compartments. Patient characteristics, activity level, functional instability, treatment type, and trauma-related variables were evaluated as determinants. Results: The median time between MRI at baseline and MRI at 2-year follow-up was 25.9 months (interquartile range, 24.7-26.9 months). Progression of cartilage defects in the medial and lateral tibiofemoral compartments was present in 12% and 27% of patients, and progression of osteophytes in tibiofemoral and patellofemoral compartments was present in 10% and 8% of patients, respectively. The following determinants were positively significantly associated with early degenerative changes: male sex (odds ratio [OR], 4.43; 95% CI, 1.43-13.66; P = .010), cartilage defect in the medial tibiofemoral compartment at baseline (OR, 3.66; 95% CI, 1.04-12.95; P = .044), presence of bone marrow lesions in the medial tibiofemoral compartment 1 year after trauma (OR, 5.19; 95% CI, 1.56-17.25; P = .007), joint effusion 1 year after trauma (OR, 4.19; 95% CI, 1.05-16.72; P = .042), and presence of meniscal tears (OR, 6.37; 95% CI, 1.94-20.88; P = .002). When the patients were categorized into 3 treatment groups (nonoperative, reconstruction <6 months after ACL rupture, and reconstruction ≥6 months after ACL rupture), there was no significant relationship between the treatment options and the development of early degenerative changes. Conclusion: Two years after ACL rupture, early degenerative changes were assessed on MRI. Concomitant medial cartilage defect and meniscal injury, male sex, persistent bone marrow lesions in the medial tibiofemoral compartment, and joint effusion are risk factors for degenerative changes.